Indian consensus on the management of CRE infection in critically ill patients (ICONIC) — India. Issue 8 (3rd August 2019) - Soman, Rajeev; Veeraraghavan, Balaji; Hegde, Ashit; Jiandani, Prakash; Mehta, Yatin; Nagavekar, Vasant; Rodrigues, Camilla; Singh, R K; Swaminathan, Subramanian; Todi, Subhash; Varma, Subhash; Patil, Saiprasad; et al.
ABSTRACT: Background : The increasing burden of carbapenem-resistant Enterobacteriaceae (CRE) carriage and infection in different patient settings in India has created an acute need for guidance for clinicians regarding optimal strategies for the management of CRE infection in critically ill patients. Research design and methods : A multidisciplinary panel of 11 Indian experts in CRE infection assembled for comprehensive discussion and consensus development. The experts developed clinical statements through a systematic review of key literature. Main outcome measures : The panel voted anonymously on 60 clinically relevant questions, through a modified Delphi process. Results : Forty-six key clinical consensus statements (CCS) were proposed. The panel reached a consensus on several important issues, providing recommendations on surveillance, diagnosis, prevention, pharmacokinetic challenges, combination therapy, and cornerstone molecules in CRE infections. The panel also proposed a treatment algorithm for NDM-prevalent settings. Conclusion : These consensus statements may offer clinicians expert guidance on the management of CRE infections. There is a dearth of high-/moderate-level evidence on managing CRE infections; the recommendations presented herein are based on expert opinion.